The Prognostic Value of Body Mass Index in Patients With Urothelial Carcinoma After Surgery: A Systematic Review and Meta-Analysis - Zhiqiang Yang; Yunjin Bai; Xu Hu; Xiaoming Wang; Ping Han (Dose-Response, 2020)
Background: The clinical evidence of body mass index (BMI) for survival has increased in urothelial carcinoma (UC). This study aimed to investigate the prognostic value of BMI on the oncologic outcomes of patients with UC after surgery. Methods: The systematic review and meta-analysis was performed using Pubmed, Embase and Cochrane Library. We collected hazard ratio (HR) and 95% confidence interval (CI) on cancer specific survival (CSS), overall survival (OS) and recurrence-free survival (RFS) from the studies including upper tract urothelial carcinoma (UTUC) and urothelial carcinoma of bladder (UCB). Results: A total of 13 studies comprising over 12,200 patients were enrolled in the quantitative synthesis. Compared with normal weight, overweight was associated with better CSS (HR = 0.87, 95% CI: 0.79-0.95) and RFS (HR = 0.86, 95% CI: 0.78-0.96). Meanwhile, we found that obese patients had worse CSS (HR = 1.14, 95%CI: 1.03-1.26), OS (HR = 1.31, 95% CI: 1.19-1.44) and RFS (HR = 1.24, 95% CI: 1.12-1.37). We observed that underweight was associated with inferior CSS (HR = 1.87, 95% CI: 1.54-2.26) in UTUC patients. Conclusions: Overweight was a protective factor for patients with UC after surgery, while obesity and underweight predicted unfavorable survival. Individual BMI may be considered for prognostication after surgeries and patient stratification for clinical trials.